"Lalu Lintas Pakaianku": Learning Media for Sex Education for Early Childhood - Kartika Adyani; Isna Hudaya; Noveri Aisyaroh (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The increase in sexual violence against children makes sex education for early childhood an increasingly serious and urgent subject. It is caused by the lack of educational media for sex education. Puppets are the right media for learning because they can further develop imagination and absorption, and teach children to empathize. This study aimed to find out whether the puppets “Lalu Lintas Pakaianku” were suitable to be used to help parents or teachers provide sex education in early childhood. The Development Research was applied in this study. The results showed that the media of "Lalu Lintas Pakaianku” hand puppet were valid  and the manual book indicated a valid category so that the media could be used as the learning media of sex education in early childhood